Animal experimentation-Part II: In periodontal research - T K Pal (Wolters Kluwer Medknow Publications, 2015)
Animals contribute to the development of medical and dental sciences by being sacrificed in the hands of scientists. The experimental design demands a specific type of animal to be used for experimentation. Each animal needs proper handling, care, and diet. Alongside specific advantages and disadvantages pertaining to each type of animal need to be understood well depending on the type of study/experiment. It is important for the researcher to know the disease susceptibility of each animal. The purpose of this paper is to highlight the salient factors that need to be considered for animal experimentations.